A collaborative perspective for autonomy in teaching and learning - Ng, Kwei Kuen (Penerbit UKM, 2005)
This chapter examines how autonomy as a teaching-learning concept can prevail in a predominantly teacher-centered learning environment at the tertiary level. To do so, a comprehensive collaborative paradigm is used to highlight the inter-relationships between the players, the language and the subject in an EAP context. This will demonstrate how instructors and learners can explore autonomy first separately then together. The observations and experiences gathered over a two-year period in a tertiary institution in Malaysia provide the body of data on which this chapter is based. The findings suggest that autonomy, in particular learner autonomy, cannot be “taught.” It needs to be developed by the teacher suppressing the desire to lead, and overcoming her phobia of uncertainty. Additionally, the language teacher must be prepared to collaborate with the subject lecturer to authenticate the learning goals.